"We Are All Carrying Someone Else's Child!": Relatedness and Relationships in Third‐Party Reproduction. Issue 1 (18th January 2016) - Berend, Zsuzsa
ABSTRACT: In this article, I explore surrogates' rich, diverse, and collective negotiations of relatedness and relationships on the largest U.S. surrogacy support website. Surrogates reconfigure existing kinship understandings and maintain that intent and love are firmer bases of parenthood than biogenetic connection. Increasing use of donor gametes contributes to the emphasis on desire to be parents. In gestational surrogacy, genetic relatedness between the child and the intended parents strengthens claim to parenthood but lack thereof does not call parenthood into question. Traditional surrogates' biogenetic connection to the child they carry is never considered to be grounds for claims to motherhood. Surrogates and intended parents "do kinship" and consider the actions of kinship more consequential that its biological facts. In their accounts, desire for children is "natural" and the choice to raise them is understood as morally positive. Genetic facts, however, are understood as morally neutral. Surrogates and intended parents contend that surrogate babies belong to the parents who want them. Surrogates' emphasis on chosen solidarity works to diminish the importance of genetic relatedness and helps them uphold the traditional boundaries of their own nuclear family and that of the intended parents. [ kinship, assisted reproduction, U.S. surrogacy, family ]